Emails and death: Legal issues surrounding post-mortem transmission of emails. Issue 7 (9th August 2019) - Harbinja, Edina
Abstract: The paper is a first thorough examination of what happens to one's emails on death. The paper demonstrates that some content of emails can be protected by copyright and transmitted on death accordingly. The paper then analyzes the contractual provisions of the main email providers, Google and Microsoft, in order to determine how these contracts, regulate the transmission of emails on death. The author finds that these provisions complicate the issues of property and transmission of digital assets and do not offer a meaningful control over the assets for their users. The paper adopts a novel focus introduced in the author's earlier research, the idea of post-mortem privacy that is the right to privacy after death. This concept serves as an argument against the default transmission of emails on death without the deceased's consent, whether through the laws of intestacy or by requiring the service providers to provide access to the deceased's emails. Finally, the paper canvasses a solution which combines law and technology. It is argued that much more control should be placed in the hands of emails users. Post-mortem privacy, a potentially contested phenomenon, only accentuates the need to better account for the interests of the deceased, having in mind the volume of personal data and personal nature of emails. Therefore, an in-service solution is promoted, backed up by policy and legislation.